La planificación de la acción humanitaria, o si la lechera hubiera usado el marco lógico - Rey Marcos, Francisco (Revista Española de Desarrollo y Cooperación, 2023)
The article tries to show a general overview of planning issues in the humanitarian sector, focusing on some of the new quality initiatives promoted in recent years. At the same time, in more general terms, it makes some reflections about the challenges and problems that the improvement of quality in this sector has to face.